2005
DOI: 10.1111/j.1444-0938.2005.tb06713.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of age‐related maculopathy using subjective vision tests

Abstract: This paper reviews non-standard, clinical vision tests that may be used to detect the earliest visual loss in age-related maculopathy (ARM), before fundus changes are detected. We recommend a clinical test battery for all patients aged 60 years and older, comprising low luminance/low contrast (SKILL) VA or low contrast VA, desaturated D-15 colour vision assessment, flicker perimetry, glare recovery and dark adaptation if possible, together with conventional assessments of case history, ophthalmoscopy and high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 137 publications
0
33
0
1
Order By: Relevance
“…Além disso, habilidade de leitura tem sido incluída como padrão de medida da visão, e tem se mostrado mais sensível do que a medida da acuidade visual na detecção desses problemas (10)(11)(12) .…”
Section: Resumo Introduçãounclassified
“…Além disso, habilidade de leitura tem sido incluída como padrão de medida da visão, e tem se mostrado mais sensível do que a medida da acuidade visual na detecção desses problemas (10)(11)(12) .…”
Section: Resumo Introduçãounclassified
“…32,33 The functional results of these tests cannot be given in detail but all show an impairment of cone-or rod-mediated function (or both) in early ARM. In addition, there is preferential vulnerability of the S-cone 34,35 and rod pathway [36][37][38][39][40][41][42] in early ARM over the L-and M-cone pathway.…”
Section: Psychophysical and Electrophysiological Function Tests In Armmentioning
confidence: 99%
“…Compared with age-matched normal controls, early AMD patients have poorer low-luminance/low-contrast visual acuity, slowed word-reading rate, loss of contrast sensitivity in the mid-to high spatial frequency range, tritan color vision defects, slowed dark adaptation, slowed recovery after exposure to a glare source, and loss of sensitivity to light flicker. 54,55 More recently, Dimitrov and colleagues showed that while rod dark-adaptation rate had a better sensitivity (87%), a more clinically deployable combination of 14 Hz flicker threshold and photo-stress dynamic could detect 71% of early AMD cases and took 10-28 minutes. 56 De Kinkelder and colleagues found that early AMD subjects had a significantly lower hit rate than healthy controls in a rarebit test (detecting one or two very small light spots).…”
Section: Visual Function Testsmentioning
confidence: 99%
“…35 One challenge in primary care AMD detection is to develop "non-standard, yet clinically-practical" vision tests. 55 Some of the tests mentioned require dedicated equipment or are long and arduous, thus may not fit in a busy office schedule. Another concern is test specificity.…”
Section: Visual Function Testsmentioning
confidence: 99%